ToF‐SIMS spectra multivariate analyses for the chemical characterization of microelectronic low‐k materials. (7th May 2014) - Scarazzini, R.; Lépinay, M.; Broussous, L.; Barnes, J. P.; Veillerot, M.; Jousseaume, V.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; et al.
<x xml:space="preserve">Abstract</x> Ultra‐low‐k thin films are largely used as a dielectric in microelectronic interconnections; the most advanced ones are based on a porous organosilicate SiOCH skeleton where the porosity is obtained by removing a sacrificial porogen. During integrated circuits fabrication, low‐k materials are exposed to various processes (e.g. lithography, etching, and cleaning), which modify the physical and chemical properties of these layers. A depth‐resolved chemical characterization is therefore required to understand these changes and improve the fabrication process. In this work, an industrial porous low‐k material, exposed to typical integration processes (specifically plasma etching, wet cleaning, and surface restoration) is studied. Results show that the treatments made on the samples produce small changes in the data collected by time‐of‐flight secondary ion mass spectrometry. These slight modifications have been interpreted and de‐convoluted using principal component analysis. Principal component analysis was applied to a large set of ions from mass spectra relative to a specific depth zone, i.e. the top surface, in order to characterize the near‐surface composition changing between the samples. This investigation led us to find a reduced set of ions discriminating the slight chemical differences between samples. Copyright © 2014 John Wiley & Sons, Ltd.